Culex sarpangensis, a new species of the subgenus Culiciomyia Theobald of the genus Culex Linnaeus (Diptera: Culicidae) from Bhutan - Somboon, Pradya; Saingamsook, Jassada; Namgay, Rinzin; Harbach, Ralph E (Zootaxa, 2024)
A new species of the subgenus Culiciomyia Theobald of the genus Culex Linnaeus is described from larvae found in a stream margin in Umling Gewog, Sarpang District of Bhutan. Based on morphology, the larvae are sufficiently distinct from the larvae of other species of the subgenus to be described and formally named here as Culex sarpangensis Somboon, Namgay & Harbach, sp. nov. The species is a member of the Fragilis Group. The fourth-instar larva is described, illustrated and compared with similar larvae of other species.